To Assess the Knowledge of Nurses Regarding Prevention of Osteoporosis among Nurses of Jinnah Hospital and General Hospital Lahore Pakistan - Riaz, Muhammad Shahid; Kanwal, Nabila; Rasool, Rehana Ghulam (International Journal of Social Sciences and Management, 2017)
Knowledge about disease its risk factor, sign/symptoms and different aspect of prevention and treatment with accurate information help the professional to make informed decision about the health practice. Average rate of the knowledge regarding prevention and treatment of Osteoporosis has been found among the different health professional over the world, including female Nurses. Aim of this study was to assess the knowledge of Nurses regarding prevention of osteoporosis. Cross-sectional design was used in research. Two Government hospitals Jinnah Hospital and Lahore General Hospital choosed for setting. Simple random sampling technique was used. Data was collect through written Questionnaire consist of 24 close ended question. Data analyzed by SPSS version 21. It was concluded that Nurses have moderate knowledge about risk factor and prevention of osteoporosis. The staff nurses who were young and clinical experience 5-10 years have positive about their role and skill about prevention and management of osteoporosis. Nurses believed that they have an important role in educating the public on osteoporosis prevention and management. One in four women over the age of 60 will develop osteoporosis 84.2% were agreed about that statement. Heredity plays role in development of osteoporosis; in response of this question 60% nurses were disagreed. Yet, their knowledge on different issues (e.g. signs of the disease, medication, and lifestyle problems) was moderate. Measures should be taken in order to expand nurses’ knowledge, such as education programs and postgraduate courses. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 202-209